Contemporary approaches to orthodontic treatment in complex mixed dentition cases: A comparison of clear aligners and traditional fixed appliances - Daniel De-Shing Chen; Johnson Hsin-Chung Cheng; Pyi Phyo Win (Journal of Dental Sciences)
This study examined orthodontic treatment strategies for patients in the mixed dentition phase, with a focus on the advantages and limitations of clear aligners and traditional fixed appliances in addressing complex tooth movements. Herein, three cases were reported to illustrate the complementary strengths of these treatment modalities. In Case 1, presurgical orthodontics for a patient with a cleft lip and palate was performed using clear aligners, resulting in successful rotation correction and optimal alignment. In Case 2, a noninvasive approach involving a transpalatal arch and fixed appliances was used to manage a high labially impacted central incisor without the use of temporary anchorage devices (TADs). In Case 3, a combination of clear aligners and braces were used to resolve severe crowding and an impacted canine, achieving the desired outcomes without extractions. The findings underscore the ability of clear aligners to enhance oral hygiene and enable precise tooth movement through software simulations. The integration of clear aligners and fixed appliances demonstrated improved treatment efficiency and patient comfort. Additional clinical trials are warranted to refine rotation correction techniques and evaluate the efficacy of TAD-assisted traction for impacted teeth.